Development of integrated thematic teaching material used discovery learning model in grade V elementary school - Desyandri Desyandri; Muhammadi Muhammadi; Mansurdin Mansurdin; Rijal Fahmi (Jurnal Konseling dan Pendidikan, 2019)
This research is intends develop integrated thematic learning materials by using discovery learning (DL) model in the 5th grade of elementary school. It categorize this research into research and development study. The model includes four phases, defining, designing, developing, and disseminating phases. However, it did not include the disseminating phases. The subjects of the research were 5th grade students. The results of the research show that the validity score of the learning materials developed is 3,36. Questionnaire and interviews with the teachers and the students reveal that the materials developed are practical. The score given by the teachers is 96, 43%, and by the students is 84, 5%. Based on the results, we conclude it that the integrated thematic learning materials developed by using (DL) model are valid and practical to be use in the learning process.